Апокаліптичний ідеалізм у поезії Тодося Осьмачки: тілесний аспект прочитання - Лебединцева, Н. (Літературознавчі обрії. Праці молодих учених, 2010)
The article analyses the peculiarities of portraying the existential situation of «ontological insecurity» of a personality, in particular, the opposition of dream and reality as the main characteristic feature of Todos’ Os’macha’s poetry. Certain attention is paid to the idealization of visionary world and consistent rejection of physical, material dimension of existence in the author’s imaginative worldview.